Analysis Of Spatial Distribution And Accessibility Of Public Healthcare Facilities By Using Geospatial Techniques: A Case Of Wolaiyta Sodo Town, Ethiopia. - Amanuel, Tadesse (ASTU, 2023)
Public Healthcare Facilities Are Among The Most Basic Needs Of The Public And Are Directly Related To Residents??? Health. Many Peoples Who Live In The Periphery Of Most Towns In Ethiopia Lack Efficient Healthcare Facilities. Wolaiyta Sodo Town Is One Of Those Towns Where Existing Healthcare Facilities Are Not Fully Accessible, Unevenly Distributed, And Scarce For Peripheral Dwellers A Result Of These Most Of The Peoples Are Confronted With Several Problems, Especially In The Time Of Medical Emergencies To Get The Service Immediately. This Study Aims To Evaluate The Spatial Distribution And Accessibility Of Existing Healthcare Facilities. Further, To Select New Suitable Sites In Study Areas. The Spatial Statistical Analysis, Locational Quotient And Nearest Neighborhood Analysis Methods Used For Spatial Distribution, Concentration And Patterns Respectively At The Kebele Level Of The Town. The Level Of Accessibility Investigated By Using Road Network Service Area Analysis In Terms Of Distance And Time. The Spatial Analyst Except For Digital Elevation Model And Land Use, The Rest Data Were Analyzed Through Proximity Analysis. The New Healthcare Facilities Sites Are Selected ByUsing GIS-Based Multi-Criteria Analysis Through The Analytical Hierarchy Process. The Data Used For This Study Such As Road Networks, Existing Healthcare Facilities, Population Density, Slope, Manufacturing Sites And Land Use Land Cover Data. The Results Of Spatial Pattern Analysis Nearest Neighborhood Ratio Show (Nnr=1.355265) Which Indicates A More Random Distribution Pattern Of Healthcare Facilities. The Service Area Analysis About World Health Organization 2km And 30 Minutes Recommended Maximum Distance And Time To Reach The Healthcare Facilities. Residents In Wolaiyta Sodo Town Could Get The Nearest Healthcare Facilities Within A 2km Distances Accessibility Are 125,934(42.51%) And 170,312(57.49%) Populations Are Accessible In >2km Distance. The Time Based Service Area Analysis Result Shows Populations Of 157,900 (53.3 %) Are Accessible Within < 30 Minutes And 138,347(46.7%) Populations Are Accessible In > 30 Minutes From The Total 296,246Populations. The Selected Suitable Site By Using GIS-Based Multi-Criteria Analysis Method Indicates That 773 Ha (6.75%), 2605 Ha (22.75%) And 5568 Ha (48.6%) Of The Study Area Has Been Identified As Very Highly Suitable, Highly Suitable, And Medium Suitable For Healthcare Facilities Development Respectively. The Remaining 2180 Ha (19%) And 324ha (2.92%) Of The Study Area Have Been Identified As Very Less Suitable And Unsuitable Sites Respectively. This Study Revealed That The Healthcare Facilities In The Study Area Are Unequal In Distribution, Which Indicates That It Needs Redistribution And Construction Of Additional Healthcare Facilities For Those Inaccessible Areas.
Keywords: Healthcare Facilities, Spatial Distribution, Spatial Accessibility, Geospatial Technology